The dynamic dimer structure of the chaperone Trigger Factor. Issue 1 (December 2017) - Morgado, Leonor; Burmann, Björn; Sharpe, Timothy; Mazur, Adam; Hiller, Sebastian
Abstract The chaperone Trigger Factor (TF) fromEscherichia coli forms a dimer at cellular concentrations. While the monomer structure of TF is well known, the spatial arrangement of this dimeric chaperone storage form has remained unclear. Here, we determine its structure by a combination of high-resolution NMR spectroscopy and biophysical methods. TF forms a symmetric head-to-tail dimer, where the ribosome binding domain is in contact with the substrate binding domain, while the peptidyl-prolyl isomerase domain contributes only slightly to the dimer affinity. The dimer structure is highly dynamic, with the two ribosome binding domains populating a conformational ensemble in the center. These dynamics result from intermolecularin trans interactions of the TF client-binding site with the ribosome binding domain, which is conformationally frustrated in the absence of the ribosome. The avidity in the dimer structure explains how the dimeric state of TF can be monomerized also by weakly interacting clients. The bacterial chaperone Trigger Factor (TF) is a dynamic protein and its dimer structure is unknown. Here the authors present a protocol combining NMR, computational and biophysical methods for the structural characterization of large dynamic protein complexes and show that TF forms a symmetric head-to-tail dimer.